A phase I study of sirolimus in combination with metronomic therapy (CHOAnome) in children with recurrent or refractory solid and brain tumors. Issue 4 (25th December 2019) - Qayed, Muna; Cash, Thomas; Tighiouart, Mourad; MacDonald, Tobey J.; Goldsmith, Kelly C.; Tanos, Rachel; Kean, Leslie; Watkins, Benjamin; Suessmuth, Yvonne; Wetmore, Cynthia; Katzenstein, Howard M.
Abstract: Background/purpose: To determine the maximum tolerated dose, toxicities, and response of sirolimus combined with oral metronomic therapy in pediatric patients with recurrent and refractory solid and brain tumors. Procedure: Patients younger than 30 years of age with recurrent, refractory, or high‐risk solid and brain tumors were eligible. Patients received six‐week cycles of sirolimus with twice daily celecoxib, and alternating etoposide and cyclophosphamide every three weeks, with Bayesian dose escalation over four dose levels (NCT01331135). Results: Eighteen patients were enrolled: four on dose level (DL) 1, four on DL2, eight on DL3, and two on DL4. Diagnoses included solid tumors (Ewing sarcoma, osteosarcoma, malignant peripheral nerve sheath tumor, rhabdoid tumor, retinoblastoma) and brain tumors (glioblastoma multiforme [GBM], diffuse intrinsic pontine glioma, high‐grade glioma [HGG], medulloblastoma, ependymoma, anaplastic astrocytoma, low‐grade infiltrative astrocytoma, primitive neuroectodermal tumor, nongerminomatous germ cell tumor]. One dose‐limiting toxicity (DLT; grade 4 neutropenia) was observed on DL2, two DLTs (grade 3 abdominal pain and grade 3 mucositis) on DL3, and two DLTs (grade 3 dehydration and grade 3 mucositis) on DL4. The recommended phase II dose of sirolimus was 2 mg/m 2 (DL3). Best response was stable disease (SD) in eight patients, and partial response (PR) in one patient with GBM. A patient with HGG was removed from the study with SD and developed PR without further therapy. Western blot analysis showed inhibition of phospho‐S6 kinase in all patients during the first cycle of therapy. Conclusion: The combination of sirolimus with metronomic chemotherapy is well tolerated in children. A phase II trial of this combination is ongoing.